Robust fault tolerant control allocation for a modern over‐actuated commercial aircraft. Issue 2 (23rd December 2020) - Vile, Liam; Alwi, Halim; Edwards, Christopher
Abstract: This paper presents a novel form of control allocation, designed within a sliding mode framework, for the fault tolerant control of over‐actuated systems. The control allocation is designed in such a way as to allow a subset of the actuators to remain inactive under nominal fault‐free conditions. In the event that the active set of actuators becomes unable to provide the desired performance, an adaption process takes place which allows the inactive actuators to compensate. A computationally light gradient descent algorithm is proposed to govern the adaption which guarantees that, if possible, actuator saturation is avoided and system performance is maintained, even in the event of severe actuator faults/failures. Rigorous conditions are derived, in terms of the faults/failures, uncertainties in fault reconstruction information and the adaptive process, which ensure sliding occurs in a finite time and that the resulting motion is stable. To demonstrate the effectiveness of the control scheme, a high‐fidelity blended wing body aircraft model is also proposed in this paper; this particular configuration of aircraft is nominally unstable, with poor control authority and a large amount of redundancy, making it a suitable candidate for testing reconfigurable fault tolerant control laws in the presence of input constraints.